Ugaling Pinoy: A Mobile Learning Game Application to Enhance Learning in Values Subject of Elementary Pupils - Escultor, Marites; Moises, Laura (International Journal of Educational Research & Social Sciences, 2022)
The fact that elementary students are still in the pick of their childhood who loves playing, learning values could be much easier if a game-type of learning will be used. The Ugaling Pinoy: A Mobile Learning Game Application About Edukasyon sa Pagpapakatao (Values Subject), is a mobile learning game developed to teach young children good manners and right conduct in different places and situations. This study was conducted to develop a learning game in values for elementary pupils and to evaluate its effect in their learning specifically in values subject. The system used various software to make the system more interesting and attractive to the end-users such as Basic for Android for coding, Adobe Photoshop for graphics, and Adobe Flash for animation. It was validated by ten (10) IT experts and five (5) values teachers. A total of 30 pupils were selected as the respondents of the study using purposive sampling. Mean, percentage and t-test were the statistical tools employed in the study. The result revealed that the developed learning game has a positive effect on the pupils’ learning in values subject. It was concluded that the system was user friendly and is very good in its performance. Furthermore, the study identifies positive effects of learning games - an aspect of intervention plan and demonstrates the potential of such learning games in improving the good manners and right conduct of the pupils. Keywords: learning values, mobile learning games, Filipino values, t-test